A comparative study on the outcome of mattress sutures and subcuticular sutures in caesarean and hysterectomy in obese patients - Narahari, Padmavathi; Atluri, Anilasre (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Selection of method of suturing is very important for a surgeon as it should be cosmetic, less painful, cost-effective and with less post -operative complications. Wound complications are comparatively more in obese than in non-obese patients. This has led to an increase in hospital stay and health cost for the patient. Hence selection of proper suture technique which would result in most favourable outcomes with least complications is of utmost importance. This study aimed to compare the outcome of subcuticular and mattress suture in obese patients. Methods: This was a retrospective study on 50 obese patients who underwent primary caesarean or hysterectomy with no previous surgeries in the past. Purposive sampling method was used for selection of patients. The wound was assessed by induration, wound discharge, infection, gaping, need for resuturing. All the patients underwent standard post-operative care. Statistical analysis was done by descriptive and inferential statistics. Results: Among the patients with subcuticular sutures, 15(60%) had wound induration with severe pain, 10 (40%) developed wound discharge, 6 (24%) had wound gaping and 6 (24%) required resuturing. Among the group with mattress sutures, 7 (28%) had wound induration, 3 (12%) developed wound discharge, 1 (4%) had wound gaping and required resuturing. Conclusions: Not only was wound induration and pain higher among the patients with subcuticular skin sutures but these patients had a significant increase in wound gaping and resuturing also when compared to the patients who had undergone closure with mattress skin sutures.